2018
DOI: 10.1089/pop.2017.0196
|View full text |Cite
|
Sign up to set email alerts
|

Non–Face-to-Face Chronic Care Management: A Qualitative Study Assessing the Implementation of a New CMS Reimbursement Strategy

Abstract: Diabetes and its comorbidities are leading causes of morbidity and mortality in the United States and disproportionately in Louisiana. Chronic care management (CCM) efforts, such as care coordination models, are important initiatives in mitigating the impact of diabetes, such as poorer health outcomes and increased costs. This study examined one such effort, the Centers for Medicare & Medicaid Services' non-face-to-face CCM reimbursement program, for patients with diabetes and at least 1 other chronic conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 6 publications
(7 reference statements)
1
35
0
Order By: Relevance
“…Two studies were focused on specific cultural populations in Australia, Canada and New Zealand (Askew et al, 2016; Sheridan et al, 2019). Eight articles focused on older adults living with multimorbidity (Brown, Stainer, Stewart, Clacy, & Parker, 2008; Greenfield et al, 2014; Hjelm, Holst, Willman, Bohman, & Kristensson, 2015; Newbould et al, 2012; Scholz Mellum, Martsolf, Glazer, Tobias, & Martsolf, 2018; Sefcik et al, 2018; Spoorenberg et al, 2015; Yeager et al, 2018). Eight articles reported interventions targeting participants deemed to be at high risk of hospital admission (Gowing, Dickinson, Gorman, Robinson, & Duncan, 2016; Grinberg, Hawthorne, LaNoue, Brenner, & Mautner, 2016; Hjelm et al, 2015; Hudon, Chouinard, Diadiou, Lambert, & Bouliane, 2015; Hudon et al, 2018; Mao et al, 2017; Newbould et al, 2012; Walker et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies were focused on specific cultural populations in Australia, Canada and New Zealand (Askew et al, 2016; Sheridan et al, 2019). Eight articles focused on older adults living with multimorbidity (Brown, Stainer, Stewart, Clacy, & Parker, 2008; Greenfield et al, 2014; Hjelm, Holst, Willman, Bohman, & Kristensson, 2015; Newbould et al, 2012; Scholz Mellum, Martsolf, Glazer, Tobias, & Martsolf, 2018; Sefcik et al, 2018; Spoorenberg et al, 2015; Yeager et al, 2018). Eight articles reported interventions targeting participants deemed to be at high risk of hospital admission (Gowing, Dickinson, Gorman, Robinson, & Duncan, 2016; Grinberg, Hawthorne, LaNoue, Brenner, & Mautner, 2016; Hjelm et al, 2015; Hudon, Chouinard, Diadiou, Lambert, & Bouliane, 2015; Hudon et al, 2018; Mao et al, 2017; Newbould et al, 2012; Walker et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, some articles in our review called for more research to ensure generalisability of the findings (Mao et al, 2017; Scholz Mellum et al, 2018; Yeager et al, 2018). We have two concerns about this approach: Qualitative studies are inherently context‐driven (Carminati, 2018; Crabtree & Miller, 1999), and arguably any results open to researcher interpretation are unable to be generalised.…”
Section: Discussionmentioning
confidence: 99%
“…Based in our study's projected costs, to be adequately compensated by CCM payments, programs would need to maintain a minimum of 50 patients per CTN in regions similar to Nebraska and a higher number in regions similar to California. In addition, CCM does not account for costs associated with staff turnover, adapting electronic medical systems to document non–face‐to‐face care management activities, and multiple providers (only one provider can bill for services in a month) . Finally, the requirement of 24/7 access to providers and the cost sharing required of patients may be significant barriers for some health systems .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CCM does not account for costs associated with staff turnover, adapting electronic medical systems to document non-face-to-face care management activities, and multiple providers (only one provider can bill for services in a month). 25 Finally, the requirement of 24/7 access to providers and the cost sharing required of patients may be significant barriers for some health systems. 13 Some have suggested that payments for collaborative dementia programs need to be restructured altogether, by moving away from fee for service toward a per beneficiary monthly payment that would include a comprehensive range of reimbursable services.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the positive effects on goal-directed care, utilization, and cost, and positive patient and provider feedback, the CCM program remains grossly underutilized. [4][5][6][7] The primary aim of this study was to develop a technology and integrated clinical staff platform (Chronic Care Management, Inc, Cleveland, OH [CCMI]) to enable a scalable, evidence-based implementation of the Medicare CCM program and to examine factors associated with hospitalization.…”
Section: Introductionmentioning
confidence: 99%